NEW WOMAN AS PORTRAYED IN SUDHA MURTHY’S MAHASHWETA - P. Poorna Jothi; Selvi, Karthigai (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The representation of women in Indian fiction, from ancient to contemporary times, can be discerned through various literary works authored by numerous writers. The depiction of women has undergone a significant transformation, transitioning from a portrayal of women enduring hardship, suffering, and exhibiting no signs of respite to one where women triumph over the challenges posed by dominant forces. In current literary discourse, female characters have been depicted as resilient and emancipated individuals. This paper focuses on the theme of female empowerment in Sudha Murty’s novel Mahashweta. Moreover, the present study sheds light on the central character whose emancipation from societal stigmatization and prejudice is depicted through her unwavering optimism, tenacity, and bravery. The primary objective of this study is to demonstrate the resilience and determination exhibited by women in overcoming various challenges in their lives.